(untitled) - Rich, Linvil Gene (New York, 1963)
This book is a companion piece to Unit Operations of Sanitary engineering. Whereas the latter book deals only with physical processes, Unit processes of sanitary Engineering covers the chemical and biological processes common to many water and waster treatment systems.
Keywords: Kỹ thuật vệ sinh,Sanitary engineering